COMPREHENSIVE ANTI-CRISIS MANAGEMENT STRATEGY AT THE MACHINE-BUILDING ENTERPRISES IN THE CONDITIONS OF CHANGES - SAKUN, LESIA; VIEDIENINA, YULIIA; SUKHOMLYN, LARYSA; TSYMBAL, OLEKSANDR (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The article is devoted to the construction of the structural elements of an anti-crisis strategy at machine-building enterprises in the face of changes, both external and internal, and is designed to maintain a stable position at such enterprises through the successful implementation of the ideas indicated in it.A comprehensive study of the concept of an economic crisis was carried out, its types were distinguished and signs were given by which one can determine its beginning at an enterprise: lack of clarity regarding the causes due to their multiplicity and the consequences of an organizational crisis; crisis situations are unlikely, but they threaten the integrity and existence of the enterprise; crisis situations limit the time for collecting information and localizing the consequences of crises; the crisis modifies or even paralyzes the work of the management team; the crisis requires the management to make quick decisions that have important consequences at the enterprise. The state of the machine-building complex of Ukraine was also analyzed, the main problems were identified, such as the emergence of a trend towards a general decrease in the number of personnel, outdated equipment and a high level of wear and tear of fixed assets, unstable, spasmodic dynamics of financial indicators of enterprises. The necessity and relevance of the topic under study in the realities of today is determined. Currently, there is an increase in crisis phenomena in the medium and large sector of the machine-building complex, which is reflected in a sharp increase in the total damage from their activities in 2020. This factor stimulates the management of machine-building enterprises to make balanced and compromise decisions in the face of external and internal changes to avoid or overcome the crisis at their own enterprises and maintain their economic position in a balanced state. Strategic solutions are proposed for getting out of the crisis or for preventive work to prevent crisis phenomena at Ukrainian machine-building enterprises.
Keywords: machine building; enterprise; management; strategy; in the conditions of changes; crisis